Penerapan Metode Statistik Dalam Evaluasi Kinerja Jembatan Dengan Menggunakan Data Pemeliharaan Dan Inspeksi - Daeli, Jefri Rahmat; Giawa, Jun Fajar Krisman; Mendrofa, Kevin Berkat; Zebua, Dermawan; Ndruru, Agusrahmat; Ziliwu, Ingat Selamat; Zebua, Cristopher (CV. SINAR HOWUHOWU, 2024)
The application of statistical methods in bridge performance evaluation is crucial to ensure the safety and sustainability of infrastructure. This study examines the use of statistical analysis to evaluate bridge performance based on maintenance and inspection data obtained from various sources. By utilizing statistical techniques such as regression analysis, hypothesis testing, and multivariate analysis, this research aims to identify factors influencing bridge performance, as well as predict future maintenance needs and lifespan. The data used includes information on the physical condition of the bridge, maintenance history, and results from visual and structural inspections. The findings of this study are expected to provide better insights into effective and efficient bridge maintenance planning, as well as offer a solid foundation for decision-making in bridge infrastructure management